(untitled) (ART AND CULTURE BULLETIN, 2023)
The article outlines the criteria for the formation of musical taste of pedogogs in musical schools. Basically, it is said about the extent to which the formation of musical taste has reached us from history to us the criteria for which it is currently developed and embodied.